(untitled) (Journal of Universal Excellence, 2026)
Research Question (RQ): What kind of research activities were conducted on Faculty of organisation studies in Novo mesto (FOS) in the last few years? Which research methodologies were implemented most frequently? Purpose: Research activities are essential for a higher education institution. This article presents the most common research questions, the most important topics and methodologies (quantitative, qualitative, and mixed methods) in doctoral dissertations. Method: The systematic research review of successfully defended and completed doctoral dissertations at the Faculty of Organisation Studies (FOŠ) was used as the research methodology. Results: 35 students received their doctorates at FOŠ. There were more women (54.3%). Five students (14.3%) were foreign nationals. Quantitative methods were most often used (71.4%), mixed methods follow (25.7%), and the qualitative method was used only once. The survey was most often used for data collection, and IBM SPSS was most commonly used for analysis. Organization: FOŠ will be provided with an overview of the research activities in the last few years. This will help management in directing further research. Society: FOŠ can contribute a great deal in increasing innovations at society’s level. Originality: This is the first such research at the Faculty of Organisation Studies and one of a few in society. Limitations / further research: The research is unique. We need additional research on this area, namely because of the importance of innovation.